Zmeny izokinetické síly flexoru a extenzoru kolene u vrcholových hrácek házené ve vybraných obdobích rocního tréninkového cyklu - Vilimova, T. (Universität Olomouc, 2016)
The objective of the thesis is to assess the dynamics of changes in isokinetic muscle strength of the knee joint flexors and extensors in terms of health and performance, focusing on bilateral and ipsilateral imbalance in elite female handball players at the end of the competition period, at the beginning of the preparatory period and at the end of the preparatory period. Muscle strength of the knee joint flexors and extensors was measured for the female players of DHK Zora Olomouc (n=1; mean age 23,09±3,48) using the isokinetic dynamometer IsoMed 2000 (D. & R. Ferstl, GmbH, Hemau, Germany) at an angular velocity of 60°/s. For evaluation, peak torque parameters were used (PT - peak torque, [N·m]). Ipsilateral muscle imbalances were assessed using the conventional H/Q ratio (H/QCON), functional H/Q ratio (H/QFUNC) and functional H/Q ratio (Hcon/Qecc) and bilateral strength percent deficit in relation to the stronger LL (%Def). The results of Freedman`s ANOVA revealed a significant effect of time on the PT values during the concentric contraction of the flexors of the dominant lower limb (DLL), of the extensors of the DLL and of the extensors of the nondominant lower limb (NLL), as well as on the H/QCON values between measurements of the DLL and on %Def values of the flexors during concentric muscle contraction. A more detailed analysis confirmed a significant increase of the PT values during concentric contraction of the flexors of the DLL between the first and the third measurements, of the extensors of the DLL between the second and the third measurements and of the extensors of the NLL between the first and the third measurements, and the second and the third measurements. A more detailed analysis also revealed a significant increase in H/QCON values of the DLL between the first and the second measurements, and the first and the third measurements as well as a significant reduction in %Def values of the flexors during the concentric muscle contraction between the first and the third measurements and of the extensors during the concentric muscle contraction between the first and the second measurements. These results show a sufficient stimulation of the maximum concentric strength of the flexors of the DLL during the preparatory period, which was reflected in reduction of both ipsilateral and bilateral muscle imbalances.